Experimental study on unsaturated direct shear and California bearing ratio tests with suction monitoring on sand-kaolin clay mixtures - Purwana, Yusep Muslih (Curtin University, 2013)
The laboratory study on unsaturated soil may comprise the study of devices or apparatus used and the study of the behaviour of soil itself. In both, suction is the main issue of the study’s concern. One of the common devices for unsaturated soil strength-testing is a suction-controlled direct shear box. With this device, suction is generated by controlling water pressure and air pressure during the test. A relatively rare method in unsaturated soil testing is suction-monitored direct shear. In this test, soil suction is not controlled; rather it is directly monitored by attaching the tensiometer to the top cap of the shear box.For flexible pavement design, a very common laboratory test is the California Bearing Ratio (CBR). The CBR has been used as a semi-empirical approach for predicting the bearing capacity of sub-grade soil since the 1920’s. The effect of water content on the CBR is commonly investigated in this type of study. Even though suction is one of the key parameters affecting unsaturated soil behaviour, the effect of soil suction on the CBR is not usually taken into account. This may be due to the difficulty in measuring soil suction while the performing the CBR test.The main objective of this study is to review the behaviour and capability of a suction-monitored direct shear device and to introduce a modified CBR test device in which suction is taken into consideration during the test. A series of laboratory tests was carried out consisting of a saturated direct shear test, an unsaturated direct shear test, and a suction-monitored CBR test on both soaked and unsoaked CBR using the artificial soil of sand and sand-kaolin clay mixtures. During the tests, suction was generated naturally by controlling the specimen in different water content values. For this, the soil water characteristic curve (SWCC) was a very useful tool for predicting the desired specimen water content and/or matric suction.Suction-monitored direct shear and CBR devices were successfully used for the specimens where matric suction was less than 80 kPa. The tensiometer performed effectively during the test. The results indicated that the presence of kaolin clay in the mixture, to some extent, led to the increase in unsaturated shear strength and the CBR. In general, matric suction versus unsaturated shear strength and matric suction versus CBR curves exhibited bi-linear curves with the inflection points occurring around the air entry value (AEV).The correlation between CBR and unsaturated shear strength was developed by plotting the failure envelopes resulting from unsaturated direct shear and unsaturated CBR tests. The range of R-square was between 0.87 and 0.99. The high R-square value of the equations indicated that the correlations were reasonable. This correlation may be applicable only for these particular specimens in the range of suction between 0 and 80 kPa.